THE IMPACT OF INTEGRATED COURSE ON STUDENT ACHIEVEMENT - Nazarova Ziyoda, Nazarova Ziyoda (Журнал иностранных языков и лингвистики, 2021)
The article examines a blended learning concept for a university teacher training course for EFL teachers. The concept points at purposeful learning using different methods and activities, various traditional and electronic media, learning spaces covering contact and distance learning, and task-based learning modules that begin with multimedia-based case stories.